Multi-code analysis of scrape-off layer filament dynamics in MAST. (19th August 2016) - Militello, F; Walkden, N R; Farley, T; Gracias, W A; Olsen, J; Riva, F; Easy, L; Fedorczak, N; Lupelli, I; Madsen, J; Nielsen, A H; Ricci, P; et al.
Abstract: Four numerical codes are employed to investigate the dynamics of scrape-off layer filaments in tokamak relevant conditions. Experimental measurements were taken in the MAST device using visual camera imaging, which allows the evaluation of the perpendicular size and velocity of the filaments, as well as the combination of density and temperature associated with the perturbation. A new algorithm based on the light emission integrated along the field lines associated with the position of the filament is developed to ensure that it is properly detected and tracked. The filaments are found to have velocities of the order of 1 k m s − 1, a perpendicular diameter of around 2–3 cm and a density amplitude 2–3.5 times the background plasma. 3D and 2D numerical codes (the STORM module of BOUT++, GBS, HESEL and TOKAM3X) are used to reproduce the motion of the observed filaments with the purpose of validating the codes and of better understanding the experimental data. Good agreement is found between the 3D codes. The seeded filament simulations are also able to reproduce the dynamics observed in experiments with accuracy up to the experimental errorbar levels. In addition, the numerical results showed that filaments characterised by similar size and light emission intensity can have quite different dynamics if the pressure perturbation is distributed differently between density and temperature components. As an additional benefit, several observations on the dynamics of the filaments in the presence of evolving temperature fields were made and led to a better understanding of the behaviour of these coherent structures.